Relevance of antibodies to myelin oligodendrocyte glycoprotein in CSF of seronegative cases. (12th November 2019) - Mariotto, Sara; Gajofatto, Alberto; Batzu, Lucia; Delogu, Rachele; Sechi, GianPietro; Leoni, Stefania; Pirastru, Maria Immacolata; Bonetti, Bruno; Zanoni, Mattia; Alberti, Daniela; Schanda, Kathrin; Monaco, Salvatore; et al.
Abstract : Objective: To determine the diagnostic relevance of myelin oligodendrocyte glycoprotein antibodies (MOG-Abs) in CSF of seronegative cases by retrospectively analyzing consecutive time-matched CSF of 80 MOG-Ab–seronegative patients with demyelinating disease. Methods: The cohort included 44 patients with NMOSD and related disorders and 36 patients with multiple sclerosis (MS). Two independent neurologists blinded to diagnosis analyzed MOG-Abs by live cell-based immunofluorescence assay with goat anti-human immunoglobulin (Ig) G (whole molecule) antibody. Sera were tested at dilutions of 1:20 and 1:40, and a cutoff of 1:160 was considered for serum positivity. CSF specimens were tested undiluted and at 1:2 dilution with further titrations in case of positivity. Anti-IgG–Fc and anti-IgM-µ secondary antibodies were used to confirm the exclusive presence of MOG-IgG in positive cases. CSF of 13 MOG-Abs seropositive cases and 36 patients with neurodegenerative conditions was analyzed as controls. Results: Three seronegative cases had CSF MOG-Abs (4% of the whole cohort or 7% of cases excluding patients with MS, in which MOG-Abs seem to lack diagnostic relevance). In particular, 2 patients with neuromyelitis optica spectrum disorder (NMOSD) and 1 with acute disseminated encephalomyelitis had MOG-Abs in CSF. Analysis with anti-IgG–Fc and anti-IgM confirmed the exclusive presence of MOG-IgG in the CSF of these patients. Among the control group, MOG-Abs were detectable in the CSF of 8 of 13 MOG-Ab–seropositive cases and in none of the patients with neurodegenerative disorders. Conclusion: Although serum is the optimal specimen for MOG-Ab testing, analyzing CSF could improve diagnostic sensitivity in seronegative patients. This observation has relevant diagnostic impact and might provide novel insight into the biological mechanisms of MOG-Ab synthesis.